The Role of Empowerment on Affective Commitment Moderated by Employee Engagement and Trust in Supervisors - Prambudi, Iwan Setiyawan; Ginting, Ginta; Patiro, Shine Pintor Siolemba; Yusriani, Sri; Prambudi, Muhammad Rayhan Mahardika (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to examine the influence of employee empowerment on affective commitment, moderated by employee engagement and trust in supervisors. A quantitative approach was employed, utilizing a structured questionnaire as the data collection tool. The data were collected from a purposive sample of 327 employees working at UT's central and regional offices. Before distribution, validity and reliability tests were conducted to ensure the quality of the instrument. The collected data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that employee empowerment positively affects affective commitment, and this relationship is moderated by employee engagement and trust in supervisors. Based on these findings, UT management should prioritize developing empowerment programs that foster employee engagement and maintain trust in supervisors to enhance the affective commitment of educational staff